2022
DOI: 10.1016/j.tranon.2022.101350
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic glycoxidation linked with nutrition enhances the tumorigenic capacity of prostate cancer epithelia through AGE mediated activation of RAGE in cancer associated fibroblasts

Abstract: Highlights Nutrition associated glycoxidation promotes aggressive prostate tumor growth. AGEs, the final product of glycoxidation were a key pro-tumorigenic effector. Dietary-AGE mediated effects were dependent upon stromal RAGE expression. AGE-RAGE signaling caused a regulatory program of activated stroma & CAF activation. Dietary-AGE effects were reproduced using in vivo, ex vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Based on the above proteomic analysis, ARE-RAGE signaling pathway might be associated with the antitumor activity of SW1990 after the combined use of G-6 and GEM. This pathway is regulated to increase ROS [ 18 , 19 ]. However, the accumulation of ROS is thought to be related to the disruption of MMP [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above proteomic analysis, ARE-RAGE signaling pathway might be associated with the antitumor activity of SW1990 after the combined use of G-6 and GEM. This pathway is regulated to increase ROS [ 18 , 19 ]. However, the accumulation of ROS is thought to be related to the disruption of MMP [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The receptor pathway is the main pathway of AGEs, and the most studied receptor is the receptor for advanced glycation endproducts (RAGE) [ 18 ]. RAGE is expressed in cancer cells, such as pancreatic cancer and prostate cancer, and is closely related to oxidative stress in the body [ 19 , 20 ]. The development of drug-resistant pancreatic cancer can be accelerated by RAGE-initiated signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that nitrosative stress and glycoxidation of proteins are increased in obese women compared to healthy controls as well as that bariatric surgery vastly normalizes detected abnormalities in these processes [35]. Interestingly, it has been shown that nutritionally related glycoxidation increases the tumorigenic potential of different cancer types [36,37] and glycoxidation has been recognized as a contributor to the vicious cycle in the development of lung cancer [38]. A tight inverse association was shown between the body fat percentage and antioxidant capacity [34] and decreased anti-oxidative defense, together with increased nitrosative stress, was found in patients with prostate and breast cancers [39].…”
Section: Metabolic Environment In Obesitymentioning
confidence: 99%
“…However, RAGE depletion in stromal cells arrested the AGE-driven cancer cell growth. This implies the role of AGEs-RAGE in the crosstalk between tumour cell and tumour-associated fibroblasts/stroma in eliciting cancer progression and metastasis, and the role of AGE-rich diet in inciting tumorigenic events via molecular interplay of tumour micro-milieu [ 39 ].…”
Section: Metabolic Imprint Of Ages In Cancersmentioning
confidence: 99%